Does stock market liberalization cause higher volatility in the Bursa Malaysia? - Law, Siong Hook; Wan Ngah, Wan Azman Saini (Universiti Malaysia Sarawak, 2008)
This study examines the impact of stock market liberalization on stock return volatility in the Bursa Malaysia (formerly known as the Kuala Lumpur Stock Exchange), using the EGARCH model with sudden changes of variance during the period of 1985 - 2006. The analysis is conducted based on four sub-sample periods namely: pre-liberalization, post-liberalization before 1997-98 East Asian financial crisis, post-liberalization during crisis and post-liberalization during capital control periods. The empirical results indicate that stock return volatility fell after the Bursa Malaysia was opened up to foreign investors. However, the volatility has increased during the financial crisis period. The selective capital controls and pegging of the currency have led to upswing in the Kuala Lumpur Composite Index, which helped to reduce the stock return volatility.